2012
DOI: 10.1159/000339573
|View full text |Cite
|
Sign up to set email alerts
|

Acute Reversible Heart Failure Caused by Coronary Vasoconstriction due to Continuous 5-Fluorouracil Combination Chemotherapy

Abstract: We present the case of a 51-year-old male patient who received adjuvant chemotherapy consisting of oxaliplatin, bolus and continuous 5-fluorouracil (5-FU) and leucovorin after anterior resection because of locally advanced rectal cancer. Preoperative chemotherapy with capecitabine (an oral 5-FU prodrug) had been well tolerated. Two days after initiation of the first course of chemotherapy, the patient reported typical chest pain. The ECG showed ST elevations and prominent T waves in almost all leads. Due to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Additionally, the presence of these features in the setting of drug use, excludes the diagnosis of SCM, per Gothenburg Criteria 38. A similar presentation of reversible global hypokinesis associated with 5-FU has been previously described,39–45 and these cases do not meet the strict definition of SCM (table 1). Thus, these reports of 5-FU-related global hypokinesia, make us think about our current understanding of the underlying mechanism for this cardiotoxicity.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, the presence of these features in the setting of drug use, excludes the diagnosis of SCM, per Gothenburg Criteria 38. A similar presentation of reversible global hypokinesis associated with 5-FU has been previously described,39–45 and these cases do not meet the strict definition of SCM (table 1). Thus, these reports of 5-FU-related global hypokinesia, make us think about our current understanding of the underlying mechanism for this cardiotoxicity.…”
Section: Discussionmentioning
confidence: 69%
“…The mechanisms of 5-FU-induced cardiotoxicity are hemorrhagic infarction, myocardial inflammatory reaction with interstitial fibrosis; arterial endothelial injury followed by thrombosis (Bertolini et al, 2001); increased metabolism leading to depletion of ATP, increased levels of superoxide anion and a decreased antioxidant capacity; arterial vasoconstriction and altered plasma levels of substances involved in coagulation and fibrinolysis (Dechant et al, 2012). Oxidative stress causes cellular damage, coronary artery spasm and the decreased affinity of RBCs to transfer oxygen, resulting in myocardial ischemia, cardiac arrest and sudden death (Polk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that 5-FU has direct toxic effects on vascular endothelium that involves endothelial nitric oxide synthase (NOS) and causes coronary spasms and endothelium-independent vasoconstriction through protein kinase C (Dechant et al, 2012;Lieutaud et al, 1996).…”
mentioning
confidence: 99%